Increased seroprevalence of IgG-class antibodies against cytomegalovirus, parvovirus B19, and varicella-zoster virus in women working in child day care - van Rijckevorsel Gini; Bovée Lian P; Damen Marjolein; Sonder Gerard J B; Schim van der Loeff Maarten F; van den Hoek Anneke (BMC, 2012)
Abstract Background Primary maternal infection with cytomegalovirus (CMV), parvovirus B19 (B19V), and varicella-zoster virus (VZV) may result in adverse pregnancy outcomes like congenital infection or foetal loss. Women working in child day care have an increased exposure to CMV, B19V, and VZV. By comparing the seroprevalence of IgG-class antibodies against CMV, VZV and B19V in female day care workers (DCW) with the seroprevalence in women not working in day care this study aimed to assess the association between occupation and infection. Methods A cross-sectional design was used. Out of a random sample of 266 day care centres, demographic data, data on work history, and blood samples were collected from 285 women from 38 centres. In addition, blood samples and basic demographics from women who participated in a cross-sectional survey of the Amsterdam population (2004) were used. All blood samples were tested for IgG-class antibodies against CMV, B19V, and VZV. Results Twenty-seven percent of the DCW were still susceptible to B19V or CMV. Working in day care was independently associated with B19V infection in all DCW (prevalence ratio [PR] 1.2; 95 % CI 1.1-1.3), and with CMV infection in DCW of European origin only (PR 1.7; 95 % CI 1.3-2.3). Almost all women born outside Europe tested seropositive for CMV (96 %). All DCW tested seropositive for VZV, compared to only 94 % of the women not working in day care. Conclusion This study confirms the clear association between employment in child day care centres and infection with CMV and B19V. Intervention policies, like screening of new employees and awareness campaigns emphasizing hygienic measures among DCW, should be implemented urgently to improve the maternal health of these women and the health of their offspring.